1997
DOI: 10.1021/jp962801n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environment on Pressure-Induced Emission of Benzophenone, 4,4‘-Dichlorobenzophenone, and 4-(Dimethylamino)benzaldehyde in Solid Media

Abstract: The pressure-induced emission of three aromatic carbonylssbenzophenone (BP), 4,4′-dichlorobenzophenone (DCBP), and 4-(dimethylamino)benzaldehyde (DMABA)sdissolved in solid polymers and also in their crystalline state has been studied. Under pressure all compounds dissolved in polymers reveal a significant enhancement of the luminescence emission in the low-pressure region. The degree of increase is strongly dependent on the type of polymer. DMABA exhibits both fluorescence and phosphorescence, whereas BP and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the DFBP-doped PMMA film, the luminogens are molecularly dispersed and are physically shielded and protected from the attacks from oxygen and water by the polymer matrix. However, the luminogen is still nonemissive at room temperature . Furthermore, its spots adsorbed on the TLC plates remain incapable of emitting light even after they have been placed under a nitrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…In the DFBP-doped PMMA film, the luminogens are molecularly dispersed and are physically shielded and protected from the attacks from oxygen and water by the polymer matrix. However, the luminogen is still nonemissive at room temperature . Furthermore, its spots adsorbed on the TLC plates remain incapable of emitting light even after they have been placed under a nitrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that, given the lifetime of triplet states, much of the quenching is via vibrational coupling to the matrix which coupling increases with compression. 11 If the emission efficiency from E 2 is less than that for Kt, the increasing fraction of E 2 at higher pressures could contribute to the modest decrease in I T observed from 30 to 60 kbar.…”
Section: Resultsmentioning
confidence: 96%
“…However, nothing is known about the nonradiative rate from E 1 , and the literature 4 indicates that the nonradiative rate from the excited state 1 Kt to 0 E 1 may be via 3 Kt and 3 E 1 . It has been shown that, given the lifetime of triplet states, much of the quenching is via vibrational coupling to the matrix which coupling increases with compression . If the emission efficiency from E 2 is less than that for Kt, the increasing fraction of E 2 at higher pressures could contribute to the modest decrease in I T observed from 30 to 60 kbar.…”
Section: Resultsmentioning
confidence: 99%
“…The samples and their preparation have been described in the preceding paper . The light-induced experiments, either the emission or absorption, were performed in a Merrill−Bassett diamond anvil cell (DAC) at room temperature, utilizing low-fluorescence diamonds with a culet diameter of approximately 0.8 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The present paper is a continuation of our investigations of pressure and light induced effects on luminescence of molecules with nonbonding electrons dissolved in solid media. The general interest in this class of molecules has stemmed mainly from their prolific triplet state features providing a variety of excellent examples for that kind of photophysical and photochemical studies like singlet−triplet intersystem crossing, triplet−triplet annihilation, energy transfer and migration, triplet-state absorption, and triplet-state photoreactivity via the hydrogen abstraction and/or α-cleavage reactions. As we have shown, for some of these processes, they can be significantly perturbed under external hydrostatic pressure providing new information inaccessible at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 96%